2019
DOI: 10.1152/japplphysiol.00633.2018
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate attenuates acid-induced augmentation of the mechanical response in rat thin-fiber muscle afferents in vitro

Abstract: Exercise-induced tissue acidosis augments the exercise pressor reflex (EPR). One reason for this may be acid-induced mechanical sensitization in thin-fiber muscle afferents, which is presumably related to EPR. Acid-induced sensitization to mechanical stimulation has been reported to be attenuated in cultured primary-sensory neurons by exogenous chondroitin sulfate (CS) and chondroitinase ABC, suggesting that the extracellular matrix CS proteoglycan is involved in this sensitization. The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…Consistent with previous studies (Matsuda et al 2015;Hotta et al 2019), we confirmed that I.M. administration of the control solution did not affect mechanical responsiveness.…”
Section: Muscle-nerve Preparationsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies (Matsuda et al 2015;Hotta et al 2019), we confirmed that I.M. administration of the control solution did not affect mechanical responsiveness.…”
Section: Muscle-nerve Preparationsupporting
confidence: 92%
“…Although group IV afferent fibres are generally more metabolically-sensitive and group III fibres more mechanically-sensitive Jankowski et al 2013), group IV fibres are polymodal in nature with many similarly responding to mechanical stimuli (Kumazawa & Mizumura, 1977). Moreover, group IV fibres are plentiful and more easily identified in the preparation utilized (Taguchi et al 2005;Hotta et al 2015Hotta et al , 2019Matsuda et al 2015). These two characteristics form the rationale for assessing group IV muscle afferent responsiveness in the present study.…”
Section: Figure 1 Local Application Of Control Solution Did Not Chanmentioning
confidence: 94%
See 3 more Smart Citations